2021
DOI: 10.5194/se-12-2351-2021
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 2020 COVID-19 lockdown measures on seismic noise recorded in Romania

Abstract: Abstract. After the World Health Organization declared COVID-19 a pandemic in March 2020, Romania followed the example of many other countries and imposed a series of restrictive measures, including restricting people's mobility and closing social, cultural, and industrial activities to prevent the spread of the disease. In this study, we analyze continuous vertical component recordings from the stations of the Romanian Seismic Network – one of the largest networks in Europe, consisting of 148 stations – to ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…A similar approach to highlighting the noise change at a particular frequency range can be seen in other related studies (e.g., Pandey et al, 2020;Poli et al, 2020;Somala, 2020;Yabe et al, 2020;Arroyo-Solórzano et al, 2021;Grecu et al, 2021;Kuponiyi and Kao, 2021;Nimiya et al, 2021;Pérez-Campos et al, 2021;Shen and Zhu, 2021). This is the frequency range where most of the day-to-day human activities occur like walking, traveling and other related cultural activities.…”
Section: Resultsmentioning
confidence: 83%
“…A similar approach to highlighting the noise change at a particular frequency range can be seen in other related studies (e.g., Pandey et al, 2020;Poli et al, 2020;Somala, 2020;Yabe et al, 2020;Arroyo-Solórzano et al, 2021;Grecu et al, 2021;Kuponiyi and Kao, 2021;Nimiya et al, 2021;Pérez-Campos et al, 2021;Shen and Zhu, 2021). This is the frequency range where most of the day-to-day human activities occur like walking, traveling and other related cultural activities.…”
Section: Resultsmentioning
confidence: 83%
“…Previous studies showed that during the COVID-19 lockdown there was decrease in noise levels due to the reduction of humanrelated activities, and as recorded by both broadband (Poli et al, 2020;Xiao et al, 2020;Lecocq et al, 2020;Somala, 2020;Dias et al, 2020;Roy et al, 2021;Grecu et al, 2021;Cannata et al, 2021) and strong motion (Yabe et al, 2020;Łukasz Ścisło et al, 2021) stations. These activities were affecting our stations more significantly since several of the RAN stations are located inside or near to the public buildings.…”
Section: Covid-19 Lockdownmentioning
confidence: 94%
“…Global government-imposed lockdowns to combat the COVID-19 pandemic have intensified the study of anthropogenic seismic noise, as the staggered easing of restrictions would aid the characterization of dominant noise sources. At the same time, the reduced noise levels during lockdowns make it possible to detect natural events that otherwise drown in the noise (De Plaen et al, 2021;Grecu et al, 2021) and thus improve seismic hazard estimates. Notably, in a global study of lockdown effects on seismic amplitudes, Lecocq, Hicks, et al (2020) also observed a significant reduction in seismic noise at 20 GSN stations.…”
Section: Environmental Seismology Beyond Global Networkmentioning
confidence: 99%